Osnovy mnogoletnej podgotovki junych orientirovscikov - Voronov, Ju. S. (Teorija i Praktika fiziceskoj Kul'tury, 2003)
The sports orientation - it is not running plus technique of map reading, but the interconnected complex which it is necessary to create and improve since the first years. The one of components of the efficient control by training process of young athletes is the definition of the conducting factors to the greatest degree influencing the success of the competitive activity. The carried out factorial analysis allocated at athletes-orientatiers the independent and most significant factor caused by the combination of endurance at work aerobic and anaerobic character with the level of the development of mental processes. For the creation of the base for the special preparedness of young orientatiers it is necessary to pay the special attention to the development of such means and methods of training which would provide the development of aerobic and anaerobic abilities of an organism and the specific mental qualities.